Proceedings of the Workshop on Linkages between Wastelands and Biodiversity, 16-19 September 1991, Centre for Ecological Sciences (Technical bulletin (Indian Council of Agricultural Research. National Bureau of Soil Survey and Land Use Planning) ;, 1991)
With special reference to India.